Teknik Self-Regulated Learning untuk Mengurangi Kejenuhan Belajar Siswa SMA - Nur Afifah Hilmy; Ulya Makhmudah; Agus Tri Susilo (Jurnal Psikoedukasi dan Konseling, 2022)
Abstract: This study aimed to test the effectiveness of Self-Regulated Learning Techniques in Reducing Study Saturation in High School Students. The research design used was the Prettiest-Posttest Nonequivalent Control Group Design. This design divided the research subjects into two groups, namely the experimental group and the control group, each of which consisted of five students. The research subjects were students who were bored with learning. This study used a questionnaire focused on learning fatigue in data collection techniques. Based on the results of hypothesis testing, there were significant differences between the experimental and control groups after treatment with the Self-Regulated Learning technique. The analysis results obtained from the post-test data, which were then processed using the Mann-Whitney test, showed a significance score of 0.036 (0.036 <0.05). It can be said that the Self-Regulated Learning technique can be used to reduce student learning saturation.